Extra-Legal Actions of the Security Council in Violation of Fundamental Human Rights - Seyyed Ghasem Zamani; Javad Safdari kohneshahri (پژوهشهای حقوقی)
The Security Council has interpreted the concept of international peace and security extensively and extended it to a wide range of issues, including the protection of human rights and the protection of human rights abuses. So that some of its decisions and actions have been beyond the limits of legal authority and competence and incompatible with the objectives of the Charter and human rights obligations and contrary to the standards of international law. The purpose article is to examine the Security Council as an extra-legal body and the shortcomings of its commitment to its obligations and responsibilities in the face of serious human rights violations resulting from Chapter VII and humanitarian interventions. Despite the council's claim of human rights protection, there has been a clear contradiction in its management behavior and performance, which not only has not reduced human rights violations in practice, but has in some cases exacerbated the council's inefficiency. The findings show that non-compliance with the limits and powers and veto power of the permanent members of the Council is one of the most important factors in the failure of the Security Council in resolving human rights issues and managing international crises. Therefore, by adopting a mechanism independent of the political interests of the permanent members and using the veto to strengthen and positive cooperation, we can pave the way for fundamental changes in the behavioral patterns and procedures of the council and proper internal monitoring of its actions and commitment to provided human rights obligations.